Fecal Polyomavirus Excretion in Infancy. (15th October 2014) - Vanchiere, John A.; Carillo, Berenice; Morrow, Ardythe L.; Jiang, Xi; Ruiz-Palacios, Guillermo M.; Butel, Janet S.
Abstract: Qualitative polymerase chain reaction (PCR) was used to determine the prevalence of fecal excretion of BK virus, JC virus, and simian virus 40 in 1-year-old infants. Overall, 17.8% of 321 specimens from 64.1% of 39 infants were polyomavirus positive. These data suggest that the gastrointestinal tract may be a site of polyomavirus persistence in humans.